Igneous rocks : a classification and glossary of terms : recommendations of the International Union of Geological Sciences, Subcommission on the Systematics of Igneous Rocks - Le Maitre, R. W. (Cambridge University Press, 2002)
Decades of field and microscope studies, and more recent quantitative geochemical analyses have resulted in a vast, and sometimes overwhelming, array of nomenclature and terminology associated with igneous rocks. This book presents a complete classification of igneous rocks based on all the recommendations of the International Union of Geological Sciences (IUGS) Subcommission on the Systematics of Igneous Rocks. The glossary of igneous terms has been fully updated since the first edition and now includes 1637 entries, of which 316 are recommended by the Subcommission. Incorporating a comprehensive bibliography of source references for all the terms included in the glossary, this book is an indispensable reference guide for all geologists studying igneous rocks, either in the field or the laboratory. It presents a standardised and widely accepted naming scheme that will allow geologists to interpret terminology in the primary literature and provide formal names for rock samples based on petrographic analyses. It is also supported by a website with downloadable code for chemical classifications.
Keywords: Igneous rocks -- Classification.; elektronické knihy; electronic books